Antibiotic sensitivity pattern of bacterial isolates from sputum samples of admitted patients with acute lower respiratory tract infections in a tertiary care teaching hospital of Tripura: a hospital record-based study - Debnath, Shubhaleena; Bhaumik, Debasree; Chakraborty, Maitrayee; Ghosh, Ranjib; Das, Lakshman; Bhattacharjee, Prithul (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Antibiotics are frequently used for various infectious diseases e.g., acute lower respiratory tract infection (ALRTI). But, injudicious use of antibiotics often leads to antibiotic resistance which is an emerging problem. The objective of this study was taken up to analyse the antimicrobial sensitivity pattern of pathogens isolated from the sputum samples of admitted patients suffering from ALRTI in a tertiary care teaching hospital. Methods: It is a hospital record-based study with a sample size of 393. Results: Klebsiella (52.16%) was the most common organism followed by Acinetobacter (13.49%) and Pseudomonas (13.23%) isolated from the sputum sample. Imipenem, piperacillin/tazobactam combination and gentamicin was sensitive against Klebsiella and Pseudomonas and the association were statistically significant. Acinetobacter was resistant to ceftriaxone. Conclusions: The commonest pathogens isolated from the sputum samples were Klebsiella followed by Acinetobacter and Pseudomonas. Imipenem, piperacillin/tazobactam combination and gentamicin was sensitive against Klebsiella and Pseudomonas.